Comparative Assessment of Computed Tomography and Magnetic Resonance Imaging of Spider Morph and Wild Type Ball Pythons (Python regius) for Evaluation of the Morphological Correlate of Wobble Syndrome. (August 2022) - Schrenk, Fabian; Starck, J. Matthias; Flegel, Thomas; Kiefer, Ingmar; Tebrün, Wiebke; Pees, Michael
Summary: There is general awareness of artificial selection and its potential implications on the health and welfare of animals. Despite growing popularity and increasing numbers of reptile breeds of atypical colour and pattern variants, only a few studies have investigated the appearance and causes of diseases associated with colour morphs. Ball pythons ( Python regius ) are among the most frequently bred reptiles and breeders have selected for a multitude of different colour and pattern morphs. Among those colour variants, the spider morph of the ball python is frequently associated with wobble syndrome. The aim of this study was to determine whether a morphological variant can be found and associated with the clinical occurrence of wobble syndrome in spider ball pythons, using computed tomography and magnetic resonance imaging as in-vivo diagnostic methods. Data from five spider and three wild type ball pythons was assessed and evaluated comparatively. We were able to identify distinctive structural differences in inner ear morphology in spider ball pythons, which were highly likely related to wobble syndrome. To our knowledge, this is the first report of these anomalies and provides a basis for further anatomical and genetic studies and discussion of the implications for animal welfare in reptile breeding.